PENTAHELIX DALAM PENANGANAN SAMPAH OLEH DINAS LINGKUNGAN HIDUP DAN KEBERSIHAN KOTA PEKANBARU TAHUN 2022 - Mahfuzah, Winzila; ', Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Indonesia is one of the countries that has a waste problem because the population in Indonesia is very high which ranks 4th largest in the world. Based on the Central Statistics Agency (BPS), Pekanbaru has an area of ± 632.27 km2 and the population of Pekanbaru city in 2021 amounted to 1,117,359 people with a waste production of 132,232.49 tons with details of 365.23 tons entering the Final Processing Site (TPA) every day. This research is descriptive research with a qualitative approach. The type of data is primary data, namely informants and secondary data, namely research support data. Data collection techniques were carried out by means of interviews and documentation. This research uses Ansell and Gash's Collaboration by looking at 5 indicators of the collaboration process. The results of this study indicate that the pentahelix collaboration process between the Pekanbaru City Environment and Hygiene Office with Private, Academics, Community, Society and Media has not been optimal because the process in Ansel and Gash's theory has been carried out but the process is not going well, so that the temporary results obtained are not maximized in the collaboration process. Keywords: Waste, Pentahelix, Collaboration, Handling